Anti-racist Adult Education: A Conversation with Professor Stephen Brookfield - Neustaeter, Robin; Perry, J. Adam (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2022)
In this interview with the editors-in-chief of the Canadian Journal for the Study of Adult Education, Professor Stephen Brookfield reflects on what it means to be an anti-racist adult educator.